A Representation of Enola Holmes’ Desires as Seen in the Film Entitled “Enola Holmes” by Harry Bradbeer (A Psychoanalysis Approach) - Nilam Anjani; Christiana Evy Tri Widyahening; Sumardiono Sumardiono (PT. Pusmedia Group Indonesia, 2026)
This study aimed to analyze the representation of Enola’s id, ego, and super ego, as well as the influence of her desires in the film Enola Holmes directed by Harry Bradbeer. The research employed a descriptive qualitative method with a library research approach. The primary data source was the film Enola Holmes, supported by secondary data from articles and the movie script. Data were collected through observation and documentation, then analyzed using data reduction, data display, and conclusion drawing. To ensure validity, data and theory triangulation were applied. The findings reveal that Enola’s desires are shaped by the dynamic interaction of id, ego, and super ego. Her id appears in her instinctive drive for freedom and resistance to restrictive norms; her ego is reflected in her rational thinking and problem-solving abilities; and her super ego is shown through her moral responsibility and adherence to her mother’s values. Overall, the film portrays Enola’s psychological growth as a balance between ambition, resilience, and moral development, highlighting the intersection of identity, freedom, and responsibility in her journey of self-discovery.